Pengaruh Morfologi Blok Perkotaan Terhadap Konsumsi Energi Bangunan Komersial, Studi Kasus: Kota Palu, Indonesia - Tanari, Neyman Pearson; Syafii, Nedyomukti Imam (JURNAL RUANG / ISSN : 2085-6962, 2024)
The increasing global energy demand has become one of the issues in energy saving in buildings, not least in urban blocks where buildings and other buildings can influence each other. Urban block morphology with complex parameters can affect the energy performance of buildings at the block scale. However, on the other hand, analysis of the combined effect of urban block morphology parameters on building energy consumption is still lacking. In this study, the aim is to examine the methods and results of the effect of urban block morphology on building energy consumption. First, the research workflow for urban block energy assessment with geometry parameters as the basis for energy simulation. The sample urban block model formed is a building plot in the form of a hypothetical district of office buildings, which is then classified based on site coverage and building height. After that, the use of geometry parameters to evaluate and obtain the Energy Use Intensity (EUI) value for each sample urban block model is analyzed. Then, the combined effects of urban block morphology and geometry parameters on building energy consumption are evaluated and see how much impact they have in changing building energy use values. The results and analysis show that building density and height can directly affect building energy consumption. Increasing the values of site coverage and building height parameters has a positive influence on decreasing the EUI value.